Analisis Daya Saing Komoditi Jagung di Gorontalo: Tinjauan Literatur terhadap Pasar dan Diversifikasi Produk - Ismail Makuta; Abdul Latif; Maharajab Dinul (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
The corn commodity in Gorontalo Province has an important role in supporting food security and the regional economy, however its competitiveness in national and international markets still faces various challenges. This research aims to analyze the competitiveness of Gorontalo corn commodities through a literature review of markets and product diversification. The competitiveness of corn in Gorontalo is influenced by factors such as conditions of production factors, global price fluctuations, access to modern technology and agricultural infrastructure. Even though it has great potential, most Gorontalo corn products are still sold in raw form, which reduces their added value. Product diversification, such as processing corn into flour, starch or bioethanol, can be a strategy to increase competitiveness. This research concludes that strengthening the competitiveness of Gorontalo corn requires synergy between the government, farmers and business actors, as well as the application of modern technology to increase productivity and production efficiency.